Triple-decker transition metal complexes bridged by a single carbocyclic ring - Beck, V; O'Hare, D (2004)
This paper reviews the synthesis and characterisation of triple-decker complexes with carbocyclic middle decks. The complexes are mainly of the transition metals, with some main group examples where appropriate. Only those triple-deckers with monocyclic middle ligands are considered. Studies of the complexes' properties are described where applicable. Triple-decker organometallic complexes of transition metals have attracted interest since 1972, when Werner and Salzer prepared the tris(cyclopentadienyl)dinickel cation, the first example of this class of compound. This paper reviews the literature for those triple-decker complexes which contain a single carbocyclic ligand bridging two metal centres. © 2004 Elsevier B.V. All rights reserved.